Intimate Partner Violence among Immigrant Woman: intersectional challenges in health services - Topa, Joana (2016)
In a world in progressive movement, with increasingly diverse societies, the number of women living in a multicultural and migration context is a recognized reality. Many immigrant women living in Portugal suffer intimate partner violence, however there are a lack of knowledge about these realities. This invisibility makes it difficult to understand their specific needs and difficulties. It is known that many cases of intimate partner violence remain unreported (FRA- European Union Agency for Fundamental Rights, 2014), which in the case of immigrant women may be more serious (WHO, 2014). Studies suggest that immigrant women face huge challenges related with the accessibility and use of the health services (Fonseca, Silva, McGarrigle & Esteves, 2007), namely victim support services. Considering this, this paper aims, through an intersectional lens, to create a conceptual and theoretical discussion about intimate partner violence among immigrant women as well as to explore the different barriers in the access and use of health support services.